The pattern‐recognition molecule mindin binds integrin Mac‐1 to promote macrophage phagocytosis via Syk activation and NF‐κB p65 translocation - Liu, Yuan‐sheng; Wang, Li‐fen; Cheng, Xiao‐Shen; Huo, Ya‐Ni; Ouyang, Xiao‐Mei; Liang, Lai‐Ying; Lin, Ying; Wu, Jian‐Feng; Ren, Jian‐Lin; Guleng, Bayasi (Journal of cellular and molecular medicine, 2019)
Mindin has a broad spectrum of roles in the innate immune system, including in macrophage migration, antigen phagocytosis and cytokine production. Mindin functions as a pattern‐recognition molecule for microbial pathogens. However, the underlying mechanisms of mindin‐mediated phagocytosis and its exact membrane receptors are not well established. Herein, we generated mindin‐deficient mice using the CRISPR‐Cas9 system and show that peritoneal macrophages from mindin‐deficient mice were severely defective in their ability to phagocytize E  coli. Phagocytosis was enhanced when E  coli or fluorescent particles were pre‐incubated with mindin, indicating that mindin binds directly to bacteria or non‐pathogen particles and promotes phagocytosis. We defined that 131I‐labelled mindin binds with integrin Mac‐1 (CD11b/CD18), the F‐spondin (FS)‐fragment of mindin binds with the αM‐I domain of Mac‐1 and that mindin serves as a novel ligand of Mac‐1. Blockade of the αM‐I domain of Mac‐1 using either a neutralizing antibody or si‐Mac‐1 efficiently blocked mindin‐induced phagocytosis. Furthermore, mindin activated the Syk and MAPK signalling pathways and promoted NF‐κB entry into the nucleus. Our data indicate that mindin binds with the integrin Mac‐1 to promote macrophage phagocytosis through Syk activation and NF‐κB p65 translocation, suggesting that the mindin/Mac‐1 axis plays a critical role during innate immune responses.